Fifteen new species of Sathytes Westwood from China (Coleoptera, Staphylinidae, Pselaphinae), with an updated checklist of world species - Yin, Zi-Wei; Shen, Qi (European Journal of Taxonomy, 2020)
The Chinese fauna of the pselaphine genus Sathytes Westwood (Batrisitae: Batrisini) currently includes 20 species. In this paper, 15 new species from various provinces of the country are described: S. alpicola sp. nov. (Xizang), S. australis sp. nov. (Guangdong, Guangxi), S. chayuensis sp. nov. (Xizang), S. chengzhifeii sp. nov. (Yunnan), S. huapingensis sp. nov. (Guangxi), S. linzhiensis sp. nov. (Xizang), S. maoershanus sp. nov. (Guangxi), S. nujiangensis sp. nov. (Yunnan), S. panzhaohuii sp. nov. (Xizang), S. shennong sp. nov. (Hubei), S. tianquanus sp. nov. (Sichuan), S. transversus sp. nov. (Xizang), S. valentulus sp. nov. (Guangxi), S. xingdoumontis sp. nov. (Hubei) and S. xizangensis sp. nov. (Xizang). New collection records are provided for S. longitrabis Yin & Li, 2012, S. tangliangi Yin & Li, 2012 and S. yunnanicus Yin & Li, 2012. Maps showing the distribution of the genus in China, and an updated checklist of the world species are provided.